Lower Jurassic brachiopods from the Ibero-Levantine Sector (Iberian Range): Faunal turnovers and critical bioevents - Baeza-Carratalá, J.F.; García Joral, F.; Tent-Manclús, J.E. (Journal of Iberian Geology, 2016)
Brachiopod fauna from the peri-Iberian platform system is well-known in the Late Pliensbachian-Toarcian interval. However, the diversity dynamics and the stratigraphical distribution of this group in the Ibero-Levantine Sector of the Iberian Range require more accurate analysis due to the patchy distribution of the outcrops. The abovementioned timespan involved a period of changes in long-term environmental conditions which led to a severe extinction and critical turnovers on the brachiopod fauna (ETMEE). The Ibero-Levantine sector has notable palaeobiogeographical significance as it represents the south-easternmost outcrops of the Iberian Range connecting with the Betic Domain positioned in the South-Iberian Palaeomargin. In this region, the brachiopod fauna has been arranged into six assemblages, showing a discontinuous stratigraphic distribution since its diversity dynamics is markedly conditioned by the extinction phases linked to the ETMEE: Ass. 1, recorded in the Spinatum-lower Tenuicostatum chronozones; Ass. 2, mainly recorded in the Tenuicostatum chronozone; Ass. 3, typifying the lower Serpentinum chronozone; Ass. 4, documented in the Serpentinum-lowermost Bifrons chronozones; Ass. 5, recorded in the Bifrons-Variabilis chronozones, and Ass. 6, distinctive of the Pseudoradiosa-Aalensis chronozones. The faunal succession shows strong affinities with the Euro-Boreal province, what rules out the transitional or even Mediterranean palaeogeographical affinity previously attributed to the southernmost part of this area. Amidst the main brachiopod-based bioevents must be considered the predominance of the genus Lobothyris in the pre-ETMEE assemblages, the conspicuous record of Liospiriferina? undulata, distinctive taxon of the north-African margin and, especially, the first record in the Iberian Peninsula of thecideid marker beds prior to the ETMEE. After the opportunistic strategy conducted by Soaresirhynchia bouchardi the distribution of the post-ETMEE brachiopod assemblages is markedly influenced by the depositional sequences, entailing premature turnovers and involving the earlier record of homeomorphic morphotypes of younger terebratulides and rhynchonellides